Examining systematic technological learning of Syrian textile industry. Issue 1 (29th May 2018) - Ghazinoory, Sepehr; Ali Ali, Ammar; Hassanzadeh, AliReza; Majidpour, Mehdi
Abstract : Purpose: Because of importance of technological learning for less developed countries, the notion has received increasing attention of scholars. The purpose of this paper is to investigate technological learning systematically by assessing the effect of technology transfer actors on technological learning in less developed countries context. Design/methodology/approach: The paper presents assessment model by adopting technological learning concept based on technology absorption and incremental innovation at firm level and identifying key roles of technology transfer actors (State – Scientific and technological infrastructure – Industry) that affect technological learning. The paper follows survey as research methodology. Thus, a questionnaire was addressed to 33 Syrian textile factories to examine the assessment model. Simple linear, multiple linear and ordinal regression analyses are preformed to examine relationships of model components. Findings: The regression models show notable ability of technology transfer actors to explain technological behavior of firms to accumulate operative capability and consequently to generate passive incremental innovation. The findings indicate passive technical change system of Syrian textile industry. Therefore, goal-oriented evaluation of actual technology policy is preliminary step for achieving improvements, as well as activating scientific and technological infrastructure role by enabling strong relationships with industry and supporting interactions of domestic firms of textile industry and with foreign players. Originality/value: The paper enriches technological learning literature by proposing systematic approach that sets the nature of technical change process of less developed countries in core of analysis. Moreover, it provides a guide for technological learning practices at firm level and for policymakers based on assessing actual status of Syrian textile industry.